The Socio-cultural and Political Role of Women in the Teke Kingdom XIXth - XXth Centuries - Oba Dominique (RIRAI Publisher, 2021)
The Teke company recognizes a heavy responsibility of women in their status as wife and mother and in their participation in different social, cultural and political activities. In this matrimonial society, the Teke woman is a true artist in the history of the Teke kingdom. On this subject, the political history of the Teke kingdom invokes the implication of the woman in the management of the kingdom and in the sense that the role of the woman is very noticed in this Teke civilization which continues to resist as best it can the perverse effects of globalization. As one of the last kingdoms in Central Africa, the Teke kingdom, which resisted during slavery and European penetration, has long known the importance of women. It was in this sense that it had made it possible to place her in the socio-cultural and political sphere. The Teke woman being a dynamic woman worked with great ardor, occupying an important place within the kingdom where her presence was almost noticed everywhere.